An analysis of algebra lesson: Can apples and pears be added? - Figen Bozkuş; Özlem Kalaycı; Zülbiye Toluk Uçar (Journal of Pedagogical Research)
There is a strong relationship between the quality of education, teachers’ decisions and instructional actions, and knowledge. All of them have an important role outcome of the lesson and students’ learning. The focus of this study was to discover how the process of students’ learning or incapability of learning was affected by teaching practices. Thus, the process of teaching and pre and post-lesson interviews conducted with a middle school mathematics teacher were analyzed. The data were collected through reflective interviews that were conducted with the teacher before and after the lesson as well as the video recording of the teacher’s two-hour lesson. In light of the findings, it can possibly be argued that the teacher had actions that caused incorrect learning and misconceptions. This result cannot be explained by a single factor related to the teacher. It would not be wrong to claim that the instructional decisions (decision-making processes) in the teaching and teacher’s content knowledge had decisive roles in the formation of this result, too. Therefore, the findings were discussed within the framework of instructional decisions and teachers’ content knowledge.